Survey research methods - Fowler, Floyd J.
Popular with over 49,000 readers for giving those who want to collect, analyze, or read about survey data, a sound basis for evaluating how each aspect of a survey can affect its precision, accuracy, and credibility, this new edition presents the latest methodological knowledge on survey research